Third dose of SARS‐CoV‐2 vaccine: A systematic review of 30 published studies. Issue 6 (12th February 2022) - Petrelli, Fausto; Luciani, Andrea; Borgonovo, Karen; Ghilardi, Mara; Parati, Maria Chiara; Petrò, Daniela; Lonati, Veronica; Pesenti, Angelo; Cabiddu, Mary
Abstract: We analyzed published studies on the efficacy and safety of the third dose of the COVID‐19 vaccine in various general population settings. We conducted systematic searches of PubMed and EMBASE for series published in the English language through November 15, 2021, using the search terms "third" or "booster" or "three" and "dose" and "COVID‐19" or "SARS‐CoV‐2." All articles were selected according to the MOOSE guidelines. The seroconversion risk after third doses was descriptively expressed as a pooled rate ratio ([seroconversion rate after the third dose]/[seroconversion rate after the second dose]). The search returned 30 studies that included a total of 2 734 437 vaccinated subjects. In more than 2 700 000 Israeli patients extracted from the general population, the reduction in the risk of infection ranged from 88% to 92%. Conversion rates for IgG anti‐spike ranged from 95% to 100%. In cancer or immunocompromised patients, mean IgG seroconversion was 39.4% before and 66.6% after third doses. A third dose seems necessary to protect against all COVID‐19 infection, severe disease, and death risk. Highlights: We analyzed published studies on the efficacy and safety of the third dose of COVID‐19 vaccine in various settings. A total of 30 studies that included a total of 2 734 437 vaccinated subjects. The reduction in the risk of infection ranged from 88% to 92%. In immunocompromised patients, mean IgG seroconversion was 39.4% before and 66.6% after third doses. A third dose seems necessary to protect against all COVID‐19 infection, severe disease, and death risk.